Supply Chain Management Information System Operation Model for Service Management in the Library in Thailand - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The paper about supply chain management information system operation model for service management in the library in Thailand is important for the effectiveness of the model as well as the application in actual work settings. Literature on supply chain management and information was reviewed.. The object of this paper were to develop study the efficiency development of supply chain management information system operation model for service management in the library in Thailand. A sample groups were five experts in supply chain management, five experts in Information Science and Library Science. The paper sample totaling ten experts. The paper tool was evaluation form to evaluate supply chain management information system operation model for service management in the library in Thailand comprises four components, namely main elements, Publishers, Libraries, Users of the library. The data analysed by using arithmetic mean and standard deviation. supply chain management information system operation model for service management in the library in Thailand using Back-Box technique. The overall evaluation result an supply chain management information system operation model for service management in the library in Thailand shows the overall rating mean of 3.65 which means that supply chain management information system operation model for service management in the library in Thailand is appropriate at the high level and can support sustainable information system development.